(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to identify (The Effectiveness of Using Penta Gram Strategy in The Critical Thinking Skills for Females Students of Fifth Scientific Class. The number of the sample members reached (58) students, (29) students were for the control group, and (29) students for the experimental group. The researchers chose the experimental method and one of the partial control designs for the two equivalent groups (experimental and control) with a pre and post test. The researchers also prepared a test for critical thinking skills consisting of (25) objective paragraphs of the multiple choice type with four alternatives. The validity and consistency were verified. The Keoder-Richardson equation (k-R20) was used to calculate the factor of the test stability, the t-test was used for two independent samples to process the data using the statistical program (SPSS). The following result was concluded; There is a statistically significant difference between the average scores of the pre and post tests of the critical thinking skills of the students of the experimental group for the benefit of the post, which indicates that the Penta Gram strategy is effective in improving the level of critical thinking among the students of the experimental group, and in light of this , the null hypothesis was rejected .